2011
DOI: 10.17221/100/2010-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of triticale to wheat leaf rust (Puccinia triticina)

Abstract: Abstract:Reactions of winter triticale cultivars mostly from central Europe to recent and old leaf rust isolates were tested in the greenhouse. In one trial 20 cultivars were tested with 8 leaf rust isolates, collected recently from official wheat and triticale trials in the Czech Republic and Slovakia. In another trial 15 cultivars were tested with 6 old leaf rust isolates, used to identify leaf rust resistance genes in wheat. The cultivars Cando, Hortenso and Tricolor, registered in the Czech Republic, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
2
7
0
1
Order By: Relevance
“…The two Pt races 3SA145 and 3SA248 collected from wheat were virulent to 49 and 52 of the triticale entries, respectively. These results support the findings by Hanzalovā and Bartoš (2011) that Pt isolates from wheat are less likely to cause disease in triticale, whereas isolates collected from triticale were found more virulent to triticale than wheat. As triticale is mostly planted as a forage crop or cover crop in vineyards in SA and therefore left unsprayed, the increased susceptibility to wheat leaf rust races can contribute to the build-up of inoculum and consequent infection of commercial wheat productions.…”
Section: Discussionsupporting
confidence: 91%
“…The two Pt races 3SA145 and 3SA248 collected from wheat were virulent to 49 and 52 of the triticale entries, respectively. These results support the findings by Hanzalovā and Bartoš (2011) that Pt isolates from wheat are less likely to cause disease in triticale, whereas isolates collected from triticale were found more virulent to triticale than wheat. As triticale is mostly planted as a forage crop or cover crop in vineyards in SA and therefore left unsprayed, the increased susceptibility to wheat leaf rust races can contribute to the build-up of inoculum and consequent infection of commercial wheat productions.…”
Section: Discussionsupporting
confidence: 91%
“…Consequently, the UPGMA dendrogram displayed two virulence groups G1 and G2 comprising isolates of mixed host origin. Hanzalová and Bartoš (2011) demonstrated that isolates of Pt collected from triticale were more virulent to triticale cultivars than isolates from wheat, and that the frequency of virulence for Lr2b among these isolates was higher. However, in our study, the frequency of virulence to gene Lr2a was significantly higher in the G2 virulence group, which comprised isolates of mixed host origin (wheat and triticale).…”
Section: Discussionmentioning
confidence: 99%
“…This disease occurs mainly on the leaf blade, producing small elliptical orange-red pustules on the upper surface and causing premature defoliation. It causes both yield losses and downgrading in quality (Hanzalová and Bartoš, 2011) and its natural populations virulence is higher on triticale in comparison to wheat (Mikhailova et al, 2009). During the evolution, plants have elaborated large number of resistant genes (R genes) as a part of their defense system.…”
Section: Introductionmentioning
confidence: 99%